PENGARUH DANA ALOKASI UMUM TERHADAP PROGRAM PENGENTASAN KEMISKINAN DI KABUPATEN SIMEULUE TAHUN 2017-2021 - Nengsi Puspita Sari; Alisman, SE, M.Si (Fakultas Ekonomi Universitas Almuslim Bireuen, 2022)
Indonesia has 34 provinces, of which Aceh is one of the provinces, with 23 districts currently. Simeulue Regency in Aceh Province, off the west coast of Aceh, is a division of West Aceh and with its inauguration in 1999, Sinabang was designated as the capital. The aim achieved in this research is to determine the influence of the General Allocation Fund (DAU) on the Poverty Alleviation Program in the 5 year period from 2017 to 2021. The use of the Simple Linear Regression Statistical Data Analysis method makes it easier for researchers to obtain the desired results, with secondary data from BPS. As a result of the research, a significant regression coefficient was obtained, which means that there is a positive relationship between DAU and poverty, where if DAU funds increase, there will also be an increase in the level of poverty. The large amount of General Allocation Funds in Simeulue Regency greatly influences the number of residents who are on the poverty line. The R-square result is 39.2% to see the magnitude of the influence, which means that the General Allocation Fund in Simeulu Regency has an influence on community poverty.